A dynamic blocking notification (BN) scheme with strategic nodes for wireless ad hoc networks - Chong, W.K. (Institute of Electrical and Electronics Engineers Inc., 2014)
The traditional RTS/CTS handshaking has been widely adopted in wireless ad hoc networks to reduce the hidden terminal problem. However, the handshaking induces the false blocking problem where adjacent nodes are deferred unnecessarily by overhearing the unsuccessful RTS packets. To mitigate these, the Blocking Notification (BN) scheme was proposed previously. In the BN scheme, the hidden and exposed receivers will broadcast the BN packets to inform adjacent nodes of their deferring status to avoid any incoming RTS packets which will not be replied by them. Nevertheless, the BN scheme itself can potentially incur redundant BN packet transmissions, energy wastage and packet collisions. The effectiveness of the BN scheme depends critically on the judicious transmission and successful reception of BN packet. In this paper, we propose an improved BN scheme that is able to dynamically assign strategic nodes the right to broadcast the BN packets. The improved BN scheme with strategic nodes attempts to minimize the BN packet transmissions and avoid collisions while maximizing their successful receptions at the intended nodes. This ensures higher energy efficiency, which is critical in ad hoc networks. Moreover, the proposed BN scheme can be deployed in any arbitrary network topology instead of a simplistic linear topology as assumed in previous works. Simulation results have shown that the proposed BN scheme with strategic nodes can significantly reduce the number of BN packet transmissions and provide energy savings of up to 60. Â© 2014 IEEE.